Pengaruh Digitalisasi Pemasaran dan Peran Sistem Pembayaran Digital Terhadap Revitalisasi UMKM - Adinda Desi Saputri; Lismayana Eryanti Siregar; Evi Beatric Dewi Zebua; Halimah Tusakdiyah Nst; Dini Aulia BR Damanik; Putri Kurnia Ridwan; Wilchan Robain (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the modern era marked by technological advances, the use of smartphones has become an important part of everyday life. This technological advancement encourages people to continue to update the way they carry out their daily activities. Smartphones make various activities easier, including long-distance communication which now feels closer thanks to sophisticated technology. This sophistication is enjoyed by various groups regardless of age or profession. The digital payment system has experienced rapid development, providing significant convenience for its users. This technology plays a strategic role in encouraging the revitalization of MSMEs by offering fast, safe, and efficient transaction solutions. In the context of developing MSME digitalization, the digital payment system not only makes it easier for business actors to manage transactions but also increases consumer convenience in shopping. With proper implementation, digital payments support the operational efficiency of MSMEs, expand market access, and accelerate the adoption of the digital ecosystem. Based on research results, the use of digital payment systems has been proven to contribute positively to the transformation of MSMEs, helping them become more competitive and able to adapt amidst changes in the increasingly digital economic landscape. This emphasizes the importance of adopting digital payment technology as an integral part of the MSME revitalization strategy. This study aims to analyze the positive impact of the use of technology, especially in online marketing, digital payment systems on the revitalization of MSMEs.